Relationship between Body Mass Index (BMI) and Physiological Mechanism of Blood Pressure in Vegetarians and Non Vegetarians - Agnes Sumarto, Tatiana; Frisca, Sanny; Pranata, Lilik (UKMC International Conference (UKMC IC) Proceedings, 2024)
The increasingly advanced world will improve human lifestyles, especially their physical, one part of body measurement is body mass index which can be used to measure a person's physical abilities, this is related to human hemodynamics, namely blood pressure, so there needs to be a clear problem solving so that the risk of disease due to blood pressure that we can know earlier by measuring body mass index, The purpose of the study is to determine the relationship between body mass index and the physiological mechanism of blood pressure in vegetarians and non-vegetarians. This type of research is a quantitative type with a survey design with a cross-sectional approach. Samples aged 18-49 years amounted to 25 vegetarians and 25 non-vegetarians, data collection of body mass index with anthropometric tools (scales and meters) while to measure blood pressure with an automatic sphygmomanometer. The results of the study showed that there was a strong positive significant relationship between body mass index and blood pressure with a p-value of 0.000, Thus, along with increasing BMI also increases blood pressure in vegetarians and non-vegetarians.